2020
DOI: 10.3390/electronics9111829
|View full text |Cite
|
Sign up to set email alerts
|

For Preventative Automated Driving System (PADS): Traffic Accident Context Analysis Based on Deep Neural Networks

Abstract: Automated Vehicles (AVs) are under development to reduce traffic accidents to a great extent. Therefore, safety will play a pivotal role to determine their social acceptability. Despite the fast development of AVs technologies, related accidents can occur even in an ideal environment. Therefore, measures to prevent traffic accidents in advance are essential. This study implemented a traffic accident context analysis based on the Deep Neural Network (DNNs) technique to design a Preventive Automated Driving Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…It is evident that with the rapid development of autonomous driving technology and the complex and variable nature of the traffic environment, the number of safety incidents and vehicle recalls for AVs continues to climb. This directly affects users' trust in the safety of self-driving technology and weakens people's willingness to purchase and use self-driving cars (Kang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that with the rapid development of autonomous driving technology and the complex and variable nature of the traffic environment, the number of safety incidents and vehicle recalls for AVs continues to climb. This directly affects users' trust in the safety of self-driving technology and weakens people's willingness to purchase and use self-driving cars (Kang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In response, scholars have proposed hypotheses to verify the intrinsic link between traffic accidents and declining acceptance 3 . In recent studies, it has been found that more and more users are concerned about the safety and stability of AVs 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tests must be performed to optimize the number of vectors in the hidden layer. In this paper, hidden vector sizes of 32, 64, 128 and 256 are studied (Minhee et al, 2020).…”
Section: Methods For Predicting the Acbcmentioning
confidence: 99%